Android Mobile Device Forensics: A Review - Tayeb, Hussein Farooq; Varol, Cihan (Ieee, 2019)
Mobile device forensics is an up-to-date multidisciplinary methodology aims at preserving, extracting, analyzing, and presenting digital evidence from mobile devices. The technique encompasses various phases, which require both deep insights into mobile devices' organization and structure as well as digital analysis and examination approaches. Modern mobile devices enable multitask computing ability that requires a suitable Operating System (OS). Nowadays, both proprietary and open source operating mobile OSs are available. The progressive growth of Android operated devices makes them a potential target for cyber-attacks. In this paper, a review of the Android mobile device forensics is presented. The study is not an exhaustive review, rather it only offers a discussion of the most influential papers in the field.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: Android; digital evidence; digital forensics; memory acquisition; mobile device